International Council for Standardization in Haematology (ICSH) laboratory guidance for the verification of haemostasis analyser‐reagent test systems. Part 2: Specialist tests and calibrated assays. (20th April 2021) - Gardiner, Chris; Coleman, Robyn; de Maat, Moniek P. M.; Dorgalaleh, Akbar; Echenagucia, Marión; Gosselin, Robert C.; Ieko, Masahiro; Kitchen, Steve
Abstract: Before a new method is used for clinical testing, it is essential that it is evaluated for suitability for its intended purpose. This document gives guidance for the performance, verification and implementation processes required by regulatory and accreditation bodies. It covers the planning and verification of specialist haemostatic tests, including factor assays, D‐dimers, direct anticoagulants and thrombophilia testing.